Tecnologie per apprendere: quale il ruolo dell'Evidence Based Education? - Antonio Calvani; Giuliano Vivanet (LED Edizioni Universitarie, 2014)
Technologies for Learning: What Is the Role of Evidence Based Education? If we ask ourselves whether technology improves learning, then evidence-based research provides us with a substantial body of knowledge, mainly derived from systematic comparisons of experimental designs. In the first part of the paper, the state-of-the-art regarding the evidence on the effectiveness of educational technology, e-learning/blended learning, digital reading, and interactive whiteboards at school (K-12), is introduced underlining the contrast between these data and the rhetoric that accompanies discussion about technological innovation in schools. The second part highlights that evaluation merely based on evidence, although necessary, is not a sufficient condition for decision-making on technological innovation in schools. The introduction of technology has different implications: it requires a careful consideration of untapped potential and involves evidence-based information with other evaluation criteria, related to reasons of utility or ethical issues and values.